Porcine peritoneal macrophages are susceptible to porcine reproductive and respiratory syndrome virus infection - Durazo-Martinez, Kassandra; Chaudhari, Jayeshbhai; Kumari, Sushmita; Vu, Hiep L. X. (Frontiers in Microbiology, 2024)
Previous studies have suggested that porcine peritoneal macrophages (PPMs) are resistant to PRRSV infection, whereas porcine alveolar macrophages (PAMs) are highly susceptible. This contrast is intriguing, as both cell types belong to the same monocyte/macrophage family. The current study aimed to investigate the host factors contributing to the differing susceptibility of PPMs and PAMs to PRRSV infection. We found that PPMs exhibit a higher frequency of CD14+ cells compared to PAMs, suggesting a more immature macrophage phenotype in PPMs. Importantly, PPMs expressed both CD163 and CD169, the key receptors for PRRSV entry, although the frequency and intensity of CD163 and CD169 expression were lower in PPMs than in PAMs. Despite these differences, PPMs were susceptible to both PRRSV-1 and PRRSV-2 isolates. Notably, PPMs susceptibility increased 10-fold when the cells were cultured for 1 day before infection. PRRSV infection in PPMs was dependent on CD163, as pretreatment with an anti-CD163 antibody significantly reduced infection. Overall, our results demonstrate that PPMs are susceptible to PRRSV infection, thereby expanding the understanding of PRRSV tropism.